THE LEARNING OF NARRATIVE TEXT USES A COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL - Dina Ramadhanti; Diyan Permata Yanda (Kantor Bahasa Lampung, 2021)
AbstractThe learning model used can be a determining factor for the success of learning in the classroom. One of the learning models used in learning to write narrative texts is the Cooperative Integrated Reading and Composition (CIRC) model. This model combines reading and writing skills in an integrated manner so that it is assumed to influence learning outcomes to write narrative texts, especially imaginary story texts. This research was a quantitative study with a correlational method. This study aims to describe students' responses to the learning model and the influence of the learning model on writing narrative text skills. The results showed that the student response to the learning model was very good with a percentage of 83.64%. The relationship between the learning model variable and the narrative text writing variable is significant and very strong seen from the correlation value range, namely 0.781. The learning model factor affects the ability to write narrative text by 61% and the remaining 39% is influenced by other factors. Collaboration carried out in groups starting from reading alternately, looking for keywords, providing responses, and writing collaborative results has a good impact on the ability to retell the content of fantasy story texts according to the story elements both oral and written.Keywords: learning, narrative text, cooperative model, CIRC AbstrakModel pembelajaran yang digunakan dapat menjadi salah satu faktor penentu keberhasilan pembelajaran di kelas. Salah satu model pembelajaran yang digunakan dalam pembelajaran menulis teks naratif adalah model Cooperative Integrated Reading and Composition (CIRC). Model ini memadukan keterampilan membaca dan menulis secara terintegrasi sehingga diasumsikan memiliki pengaruh terhadap hasil belajar menulis teks naratif, khususnya teks cerita imajinasi. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasional. Penelitian ini bertujuan untuk mendeskripsikan tanggapan siswa terhadap model pembelajaran dan pengaruh model pembelajaran terhadap keterampilan menulis teks naratif. Hasil penelitian menunjukkan bahwa respon siswa terhadap model pembelajaran sangat baik dengan persentase 83,64%. Hubungan antara variabel model pembelajaran dengan variabel penulisan teks naratif adalah signifikan dan sangat kuat dilihat dari rentang nilai korelasinya yaitu 0,781. Faktor model pembelajaran mempengaruhi kemampuan menulis teks naratif sebesar 61% dan sisanya 39% dipengaruhi oleh faktor lain. Kolaborasi yang dilakukan dalam kelompok mulai dari membaca secara bergantian, mencari kata kunci, memberikan tanggapan, dan menulis hasil kolaboratif berdampak baik pada kemampuan menceritakan kembali isi teks cerita fantasi sesuai dengan unsur-unsur cerita baik lisan maupun tulisan.Kata-kata kunci: pembelajaran, teks naratif, model kooperatif, CIRC